THE EFFECT OF THE LEARNING MEDIA AND THE ABILITY TO THINK CREATIVE OF TO THE ABILITY TO SCIENCE LITERACY STUDENT OF ELEMENTARY SCHOOL - Jajang Bayu Kelana (PrimaryEdu: Journal of Primary Education, 2018)
This study aims to determine the effect of the learning media and the ability to think creative of to the ability to science literacy student of elementary school. The study was conducted at the grade V SDN Manangga and SDN Tenjonagara Kabupaten Sumedang. Research design using experiment method with treatment by level 2 x 2. Data analysis is the two way anava. The results of this study indicate that (1) There were differences in the ability to science literacy of student of study by using ICT media with education aids. (2) There was an interactional of the learning media and the ability to think creative of the ability to science literacy student of elementary school. (3) The ability to science literacy student who have high the ability to high think creative by using ICT media  more high compare who have the ability to high think creative by using education aids.(4) The ability to science literacy student who have low the ability to low think creative by using ICT media  more low compare who have the ability to low think creative by using education aids